Management of purchasing logistics of a motor transport company - Hu, Xianbin (Харківський національний автомобільно-дорожній університет, 2024)
The relevance of the chosen topic of the qualification work is due to the fact that the efficiency of the entire business system of the enterprise, its business processes, sustainable operation and financial condition of the enterprise directly depend on the effective and correct organization of procurement management and procurement logistics in general. The paper investigates the theoretical aspects of managing the procurement activities of an enterprise; analyzes the procurement management system at the enterprise JV Kharkiv Motor Depot «Southern Railway»; proposes measures to improve the procurement management system at the enterprise JV Kharkiv Motor Depot «Southern Railway» on the basis of logistics.
Keywords: procurement; logistics; management; motor transport enterprise; stocks; procurement logistics